ANALYSIS AND FUNDAMENTATION OF NORMATIVE INTERFACES BETWEEN HALAL AND ORGANIC IN SUSTAINABLE FOOD PRODUCTION - Spadotto, Anselmo Jose [UNESP] (Escola Superior Dom Helder Camara, 2023)
Knowing that both Halal system and organic food production system have as purpose the environmental and social sustainability, this research started from the hypothesis of the existence of significant interfaces in norms and practices that govern these two systems. The objective of this research was to identify, analyze and support possible normative interfaces between these two systems. The norms related to the halal system were investigated within the Sharia, or Islamic Law, and the norms related to the organic system were researched within International Movements (IFOAM) and in guidelines of certifiers operating in Brazil. This research was classified as qualitative and exploratory in all its execution phases. The results allowed to identify five relevant interfaces: (a) nature of both halal and organic product; (b) guarantee of both halal and the organic product; (c) contaminated animal and illegal for consumption; (d) genetically modified food; and (e) slaughter of animals. Although they are interfaces, they do not have enough elements to match in fundamentals these two systems. It is concluded that, despite being sustainable, there are normative interfaces between the halal system and the organic system that show fundamental differences between them.
Keywords: animal; certification; Islam; Sharia; sustainability